The Effects of Relationship Marketing on Firm Performance: Small and Medium Enterprises (SMEs) in Bangladesh - Zainudin, Awang; Hoque Abu Shams, Mohammad Mahmudule; Sumona, Salam (2017)
Today’s entrepreneurial global economy, it is essential to acquisition and retention of customers for the survival of SMEs. Relationship Marketing (RM) is among the best marketing strategy that the SMEs should adopt since customer buying decisions do not solely based on the quality and price, but also depending on their relationship with the firm. This study aimed to empirically investigate the effects of RM on the SME Performance. A self-administered questionnaire with 22 measuring items was used in data collection. The respondents were selected randomly from the list of active SMEs in Bangladesh. A total of 384 completed and usable questionnaires were received. The study employed the IBM-SPSS-AMOS package 21.0 to analyze data and test the underlying hypothesis. The study found RM has positive and significant effects on SME Performance. Consequently, the findings suggested that there is a dire need for SMEs to concentrate on RM strategy to boost their financial performance, and hence their long term survival.